# Prove by method of induction, for all n ∈ N: 5 + 52 + 53 + .... + 5n = 54(5n-1) - Mathematics and Statistics

Sum

Prove by method of induction, for all n ∈ N:

5 + 52 + 53 + .... + 5n = 5/4(5^"n" - 1)

#### Solution

Let P(n) ≡ 5 + 52 + 53 + .... + 5n = 5/4(5^"n" - 1), for all n ∈ N

Step I:

Put n = 1

L.H.S. = 5

R.H.S. = 5/4(5^1 - 1) = 5 = L.H.S.

∴ P(n) is true for n = 1.

Step II:

Let us consider that P(n) is true for n = k.

∴ 5 + 52 + 53 + …. + 5k = 5/4(5^"k" - 1)   ...(i)

Step III:

We have to prove that P(n) is true for n = k + 1 i.e., to prove that

5 + 52 + 53 + …. + 5k+1 = 5/4(5^("k"+1) - 1)

L.H.S. = 5 + 52 + 53 + …. + 5k+1

= 5 + 52 + 53 + …. + 5k + 5k+1

= 5/4(5^"k" - 1) + 5^("k"+1)   ...[From (i)]

= (5.5^"k" - 5 + 4.5^("k"+1))/4

= (5^("k"+1) + 4.5^("k"+1) - 5)/4

= (5.5^("k"+1) - 5)/4

= 5/4(5^("k" + 1) - 1)

= R.H.S.

∴ P(n) is true for n = k + 1

Step IV:

From all steps above by the principle of mathematical induction, P(n) is true for all n ∈ N.

∴ 5 + 52 + 53 + .... + 5n = 5/4(5^"n" - 1), for all n ∈ N.

Concept: Principle of Mathematical Induction
Is there an error in this question or solution?

#### APPEARS IN

Balbharati Mathematics and Statistics 2 (Arts and Science) 11th Standard Maharashtra State Board
Chapter 4 Methods of Induction and Binomial Theorem
Exercise 4.1 | Q 13 | Page 74